"With such vigilance! With such effort!" Studying Dante 'Subjectively'. (March 2015) - B, Z G.
Abstract : Since the nineteenth century, Dante studies have been dominated by variations on a contextualizing philological and historicist critical method. The article examines the implications, and especially several of the shortcomings and blind spots, of this approach. It focuses on two closely inter-related areas of investigation that hold positions of prominence in modern-day dantismo: the study of Dante's literary and doctrinal sources and of his intellectual formation. Rather than a rebuttal of historicist scholarship, the article proposes ways in which this might be refined, in particular by paying greater attention to the practical realities of medieval (Florentine) culture, including education and scholastic institutions, the circulation of manuscripts and modes of reading, and contacts between clerici and laici .